PERKEMBANGAN BESARAN ORGANISASI PERANGKAT DAERAH (OPD) KABUPATEN PEKALONGAN (Studi Banding Implementasi PP No. 84 Tahun 2000, PP No. 8 Tahun 2003, dan PP No. 41 Tahun 2007) - Putri Wulandari Atur Rejeki (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
The Implementation PP No. 41 Tahun 2007 about OPD as the replacement of PP No. 8 Tahun 2003 and PP No. 84 Tahun 2000, provided to give comprehensive guidance for the arrangement and controlling OPD that can handle all government matter. Determinant factor of OPD based on PP No. 41 Tahun 2007 consist of 3 variables namely total number of resident, luas wilayah and APBD. Total value from those variables are 61, so based on PP No. 41 Tahun 2007 Pekalongan Government has right to have Regional Secretariat (Sekretariat daerah), consist of at most 3assistant, Secretariat of DPRD, Dinas at most 15 and Lembaga Teknis Daerah at most 10.